2011
DOI: 10.1074/jbc.m110.175018
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and Morphological Properties of Hepatitis C Virus Particles and Determination of Their Lipidome

Abstract: A hallmark of hepatitis C virus (HCV) particles is their association with host cell lipids, most notably lipoprotein components. It is thought that this property accounts for the low density of virus particles and their large heterogeneity. However, the composition of infectious virions and their biochemical and morphological properties are largely unknown. We developed a system in which the envelope glycoprotein E2 was Nterminally tagged with a FLAG epitope. This virus, designated Jc1E2 FLAG , produced infect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
360
4
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 312 publications
(384 citation statements)
references
References 74 publications
17
360
4
3
Order By: Relevance
“…167 This result is in keeping with the notion that assembly and release of HCV particles are tightly linked to host cell lipoproteins and lipids. 162,[168][169][170][171][172] Moreover, the nature of the lipidic constituents of HCV particles appears to depend on the host cell in which the virus is produced.…”
Section: O N O T D I S T R I B U T Esupporting
confidence: 75%
“…167 This result is in keeping with the notion that assembly and release of HCV particles are tightly linked to host cell lipoproteins and lipids. 162,[168][169][170][171][172] Moreover, the nature of the lipidic constituents of HCV particles appears to depend on the host cell in which the virus is produced.…”
Section: O N O T D I S T R I B U T Esupporting
confidence: 75%
“…The presence of apoB in viral particles issued from Huh-7.5 cells is still a matter of debate. Although some studies have indicated that apoB is dispensable for production of infectious particles (52) and is barely detected in viral particles derived from Huh-7.5 (9,53), other studies have revealed its importance in HCV assembly and maturation (1,11,54). Moreover, the presence of apoB on secreted HCV particles has been demonstrated in viruses derived from cultured primary hepatocytes (32) or from long term cultures of Huh-7.5 cells differentiated with human serum-containing culture media (55) and in viruses recovered from patients (7,8).…”
Section: Discussionmentioning
confidence: 99%
“…To separate viral particles from lipoproteins, we performed co-IP assays using antibodies against apolipoproteins apoE and apoB, and we quantified the captured particles by HCV RNA-specific RT-quantitative PCR. We decided to use this approach because previous papers showed that the initial capture of viral particles with anti-E2 antibodies was inefficient probably because of poor epitope accessibility (9,10). We first performed co-IP assays on non-fractionated samples using apoE or apoB antibodies.…”
Section: Hcvfrg Infectious Particles Have a Lower Density As Comparedmentioning
confidence: 99%
See 1 more Smart Citation
“…[12][13][14] Second, the phospholipid compositions of HCVcc and TRL share similar characteristics, whereas they strikingly differ from those of cellular membranes or envelopes of virus that assemble at cellular membranes. [15][16][17] Furthermore, lipoprotein lipases that specifically hydrolyse lipoprotein triacylglycerol modify HCVcc biochemical and physical features and decrease their infectivity. 18,19 Thus, both in vivo-produced and in vitro-produced HCV particles share many characteristics of lipoprotein association, but with differences in the extent of apoB association.…”
mentioning
confidence: 99%